Influences on uptake of reproductive health services in Nsangi community of Uganda and their implications for cervical cancer screening - Mirembe Florence; Faxelid Elisabeth; Mutyaba Twaha; Weiderpass Elisabete (BMC, 2007)
Abstract Background Cervical cancer is the most common female cancer in Uganda. Over 80% of women diagnosed or referred with cervical cancer in Mulago national referral and teaching hospital have advanced disease. Plans are underway for systematic screening programmes based on visual inspection, as Pap smear screening is not feasible for this low resource country. Effectiveness of population screening programmes requires high uptake and for cervical cancer, minimal loss to follow up. Uganda has poor indicators of reproductive health (RH) services uptake; 10% postnatal care attendance, 23% contraceptive prevalence, and 38% skilled attendance at delivery. For antenatal attendance, attendance to one visit is 90%, but less than 50% for completion of care, i.e. three or more visits. Methods We conducted a qualitative study using eight focus group discussions with a total of 82 participants (16 men, 46 women and 20 health workers). We aimed to better understand factors that influence usage of available reproductive health care services and how they would relate to cervical cancer screening, as well as identify feasible interventions to improve cervical cancer screening uptake. Results Barriers identified after framework analysis included ignorance about cervical cancer, cultural constructs/beliefs about the illness, economic factors, domestic gender power relations, alternative authoritative sources of reproductive health knowledge, and unfriendly health care services. We discuss how these findings may inform future planned screening programmes in the Ugandan context. Conclusion Knowledge about cervical cancer among Ugandan women is very low. For an effective cervical cancer-screening programme, awareness about cervical cancer needs to be increased. Health planners need to note the power of the various authoritative sources of reproductive health knowledge such as paternal aunts (Sengas) and involve them in the awareness campaign. Cultural and economic issues dictate the perceived reluctance by men to participate in women's reproductive health issues; men in this community are, however, potential willing partners if appropriately informed. Health planners should address the loss of confidence in current health care units, as well as consider use of other cervical cancer screening delivery systems such as mobile clinics/camps.